Improving oral healthcare: towards measurement? - Baâdoudi, F.; Maskrey, N.; Listl, Stefan; van der Heijden, G. J. M. G.; Duijster, D. (British dental journal, 2016)
Provides an overview of where dentistry is in a time of changing expectations and needs.Highlights that consistent and comparable data on treatments, prevention and oral health outcomes are not routinely collected, analysed and made available.Proposes that measures, by providing greater insight into care processes and outcomes, have the potential to improve oral healthcare.
Gesehen am 19.08.2020